2002
DOI: 10.3386/w9405
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the State Children's Health Insurance Program on Health Insurance Coverage

Abstract: This paper presents the first national estimates of the effects of the SCHIP expansions on insurance coverage. Using CPS data on insurance coverage during the years 1996 through 2000, we estimate two-stage least squares regressions of insurance coverage. We find that SCHIP had a small, but statistically significant positive effect on insurance coverage. Our regression results imply that between 4% and 10% of children meeting income eligibility standards for the new program gained public insurance. While low, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
149
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(166 citation statements)
references
References 17 publications
13
149
4
Order By: Relevance
“…The effect of a for-profit (F ) clinic is less than the first non-profit clinic, yet larger than the effect of the second non-profit clinic. 28 This is consistent with the coefficient estimates from the probit analysis of Table 3. Non-profit clinics have strong effects on each other, government clinics have a slightly weaker effect on N clinics and for-profit clinics have the smallest effect on non-profits.…”
Section: Estimates Of the Identified Setsupporting
confidence: 80%
See 1 more Smart Citation
“…The effect of a for-profit (F ) clinic is less than the first non-profit clinic, yet larger than the effect of the second non-profit clinic. 28 This is consistent with the coefficient estimates from the probit analysis of Table 3. Non-profit clinics have strong effects on each other, government clinics have a slightly weaker effect on N clinics and for-profit clinics have the smallest effect on non-profits.…”
Section: Estimates Of the Identified Setsupporting
confidence: 80%
“…The identified set is, however, smaller than the union of the individual intervals. 28 Other researchers have found similar effects of a second entrant in other markets (e.g. Mazzeo (2002) and Cohen and Mazzeo (2007)).…”
Section: Estimates Of the Identified Setmentioning
confidence: 63%
“…There is a small but growing literature assessing the effects of the SCHIP expansions on insurance coverage, with findings that show reductions in uninsurance, and accompanying reductions in private coverage ranging from a negligible amount to 50% depending on the data source, analytic approach, and year. 21,22 Recent findings suggest that SCHIP had positive spillover effects on participation in Medicaid. 23 A handful of state-specific studies examined the effects of SCHIP enrollment for children with special health care needs, finding improvements in access to care.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Cutler and Gruber, along with a number of subsequent studies, found crowdout estimates of roughly 50 percent, suggesting that half of the individuals who benefit from a public health insurance expansion would otherwise have been covered in the private market (e.g. Cutler and Gruber, 1996;LoSasso and Buchmueller, 2004;Gruber and Simon, 2008 Kolstad and Kowalski (2012a).…”
mentioning
confidence: 99%